2003
DOI: 10.1016/s0735-1097(03)00255-9
|View full text |Cite
|
Sign up to set email alerts
|

Ximelagatran versus warfarin forstroke prevention in patientswith nonvalvular atrial fibrillation

Abstract: Fixed oral doses of ximelagatran up to 60 mg twice daily were well tolerated, without the need for dose adjustment or coagulation monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(87 citation statements)
references
References 20 publications
2
82
0
2
Order By: Relevance
“…When the inherent anticoagulant factors TM and TFPI are lost on the internal surface of the atrium, supplementation of these anticoagulant molecules or their substitutes, including thrombin inhibitors, would be promising. 13 These considerations will be assessed by the ongoing large clinical trials using a thrombin inhibtor …”
Section: Discussionmentioning
confidence: 99%
“…When the inherent anticoagulant factors TM and TFPI are lost on the internal surface of the atrium, supplementation of these anticoagulant molecules or their substitutes, including thrombin inhibitors, would be promising. 13 These considerations will be assessed by the ongoing large clinical trials using a thrombin inhibtor …”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the results of a previous warfarin-controlled study of ximelagatran in patients with NVAF, 14 it was estimated that the incidence of bleeding events in the warfarin group would be 15%. Based on the assumption of a similar incidence of bleeding events with edoxaban, sample size was estimated to require 104 patients to achieve a 95% confidence interval (CI) divided by 2 for the intergroup difference determined using the Score method.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical trials showed that ximelagatran, the first oral direct thrombin inhibitor to be developed, is an effective anticoagulant for many clinical indications [19][20][21][22], it was withdrawn from the market by the manufacturer in February 2006 [23] because of fears of liver toxicity. There are, however, other direct thrombin inhibitors that are under development and will appear in its wake.…”
Section: Discussionmentioning
confidence: 99%